The Effect of Tax Sanctions, Awareness Taxpayers, and Service Facilities on Vehicle Taxpayer Compliance Motorcycle in Pasuruan Regency - Niken Salsabilla; Moh. Danang Bahtiar, S.Pd., M.Pd. (Journal of Innovative and Creativity, 2025)
This study aims to determine the effect of tax sanctions, taxpayer awareness, and service facilities on motor vehicletaxpayer compliance in Pasuruan Regency. The population of this study are motor vehicle taxpayers registered in thePasuruan area. The sampling technique uses incidental sampling. The data analysis method uses Statistical Product andService Solution (SPSS Statistics). The results of this study indicate that Tax Sanctions have an effect on Motor VehicleTaxpayer Compliance in Pasuruan Regency. While Taxpayer Awareness and Service Facilities do not affect Motor VehicleTaxpayer Compliance in Pasuruan Regency. Furthermore, Tax Sanctions, Taxpayer Awareness, and Service Facilitiestogether affect Motor Vehicle Taxpayer Compliance in Pasuruan Regency.